Gap-plasmon enhanced water splitting with ultrathin hematite films: the role of plasmonic-based light trapping and hot electrons. (1st March 2019) - Dutta, Aveek; Naldoni, Alberto; Malara, Francesco; Govorov, Alexander O.; Shalaev, Vladimir M.; Boltasseva, Alexandra
Abstract : We report the enhancement of the plasmon-assisted water oxidation photocurrent in ultrathin (10–20 nm) hematite films. Abstract : Hydrogen is a promising alternative renewable fuel for meeting the growing energy demands of the world. Over the past few decades, photoelectrochemical water splitting has been widely studied as a viable technology for the production of hydrogen utilizing solar energy. A solar-to-hydrogen (STH) efficiency of 10% is considered to be sufficient for practical applications. Amongst the wide class of semiconductors that have been studied for their application in solar water splitting, iron oxide (α-Fe2 O3 ), or hematite, is one of the more promising candidate materials, with a theoretical STH efficiency of 15%. In this work, we show experimentally that by utilizing gold nanostructures that support gap-plasmon resonances together with a hematite layer, we can increase the water oxidation photocurrent by two times over that demonstrated by a bare hematite film at wavelengths above the hematite bandgap. Moreover, we achieve a six-fold increase in the oxidation photocurrent at near-infrared wavelengths, which is attributed to hot electron generation and decay in the gap-plasmon nanostructures. Theoretical simulations confirmed that the metamaterial geometry with gap plasmons that was used allows us to confine electromagnetic fields inside the hematite semiconductor and to enhance the surface photochemistry.